PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL SERTA KEPRIBADIAN TERHADAP KINERJA KARYAWAN PADA PT. BTN (PERSERO) TBK. CABANG JEMBER - Weny Oktariani; Sri Wahyu Lelly Hana Setyanti; Sumani Sumani (BISMA: Jurnal Bisnis dan Manajemen, 2016)
Abstract: This study aims to examine the effect of emotional intelligence and spiritual intelligence and personality on the performance of employees. This research was conducted at PT. Bank Tabungan Negara (Persero) Tbk. Jember Branch. Data collection was done by distributing questionnaires to 41 respondents. The data were processed by multiple linear regression analysis. Based on the result of t test, it is known that emotional intelligence and spiritual intelligence had no effect on performance Employees, while the personality effect on employee performance. Emotional intelligence did not affect the performance of employees Because the dominant respondents is male. While spiritual intelligence had no effect because the age of dominant respondents diverged between 20-40 years. Results showed that emotional intelligence, spiritual intelligence, and personality variables simultaneously affect the employees’ performance. Keywords: Emosional Intelligence, Spiritual Intelligence, Personality and Employee Performance.